2003
DOI: 10.1105/tpc.007609
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of the Unfolded Protein Response in Arabidopsis Shows Its Connection to Important Cellular Processes[W]

Abstract: We analyzed the breadth of the unfolded protein response (UPR) in Arabidopsis using gene expression analysis with Affymetrix GeneChips. With tunicamycin and DTT as endoplasmic reticulum (ER) stress-inducing agents, we identified sets of UPR genes that were induced or repressed by both stresses. The proteins encoded by most of the upregulated genes function as part of the secretory system and comprise chaperones, vesicle transport proteins, and ER-associated degradation proteins. Most of the downregulated genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
352
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(371 citation statements)
references
References 44 publications
16
352
3
Order By: Relevance
“…Genome sequence and several microarray experiments have revealed that ERAD components similar to yeast and mammals are present in plants [19,20]. We discovered that HRD3A is the only active HRD3 homolog in Arabidopsis; however, we could not detect the complementation of yeast hrd3 mutant by HRD3A (data not shown), which may be due to the low similarity between these two proteins (29.6%).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Genome sequence and several microarray experiments have revealed that ERAD components similar to yeast and mammals are present in plants [19,20]. We discovered that HRD3A is the only active HRD3 homolog in Arabidopsis; however, we could not detect the complementation of yeast hrd3 mutant by HRD3A (data not shown), which may be due to the low similarity between these two proteins (29.6%).…”
Section: Discussioncontrasting
confidence: 42%
“…The SOS3-SOS2 complex phosphorylates SOS1, a plasma membrane Na + / H + anti-porter, which effuses excess Na + ions out of cell to reduce the salt damage to plant cells. Previous studies have shown that UPR is induced upon salt stress [18] and that many stress-related genes are upregulated by tunicamycin (TM) and dithiothreitol (DTT), two ER stress inducers [19,20]. Some proteins that have functions in both ER quality control (ERQC) and stress responses also have been identified [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The authors were unable to procure a homozygous mutant for the AtIRE1-1 gene and stated that they only obtained hemizygous plants after several generations, which led them to hypothesize that homozygous IRE1-1 plants are unviable. However, they did obtain a homozygous plant for the AtIRE1-2 gene, but it did not show an impaired response to ER stress triggered by tunicamycin or β-Mercaptoethanol measured by the induction of BiP2, bZIP60 and several PDI mRNAs known to be upregulated during the unfolded protein response (Martinez and Chrispeels, 2003;Koizumi, 2005b, Kamauchi et al, 2005). Thus, despite the early identifi cation and description of some of its molecular functions, the role of IRE1 in plants seems to be a missing link in the context of UPR.…”
Section: The Upr Signaling Mechanism In Plantsmentioning
confidence: 99%
“…21,22 Approximately three hundreds genes are upregulated upon the tunicamycin-induced ER stress in Arabidopsis. 23 To investigate whether phenotype of agb1-3 upon the tunicamycin treatment is relevant to UPR pathway, we compared expression profiles of key genes in the wild-type and the agb1-3 plants. We selected binding protein 3 (BiP3), binding protein 1 and 2 (BiP1/2), calreticulin (CRT), and calnexin (CNX) as marker genes.…”
mentioning
confidence: 99%
“…All genes encode ER-resident proteins that are known to be transcriptionally upregulated during the ER stress. 23 We treated the 7-day-old seedlings with tunicamycin for 0, 2, and 5 hours, and examined expression level of the aforementioned genes by quantitative RT-PCR analysis. We repeated experiments 4 times independently, and analyzed data all together (Fig.…”
mentioning
confidence: 99%